RECCURENT GIANT CONDYLOMATA ACUMINATA CAUSED BY HUMAN PAPILLOMA VIRUS IN HIV WITH HOMOSEXUAL MALE - Kusumaningsih, Emy; Setyowatie, Lita (Institute of Topical Disease Universitas Airlangga, 2020)
Perianal giant condylomata acuminate (GCA) is a rare clinical condition associated with low-risk Human papillomavirus (HPV) type 6 and 11 infections. Human Immunodeficiency Virus (HIV) infection is one of the risk factors for GCA, that can increase the condylomata acuminate incidence and spread caused by HPV. A 28-year-old man came with a cauliflower-like mass complaint in his perianal and anal since 2 months ago. The patient did not complain of pain or itching on the mass but often bled when defecating. The patient is a male who has sex with men (MSM) and often changes partners. He has been diagnosed with HIV since 11 months ago and regularly taking anti-retroviral drugs, Efavirenz 600 mg daily. He was also diagnosed having lung tuberculosis at the same time, got 6 months treatment and was declared cured. The venereological examination of the perianal and anal region revealed erythematous and grayish stem-shaped vegetation and papules, verrucous surface, multiple, well defined, with 3 x 1.5 x 2 cm in size. A positive act of white examination was obtained. Blood tests revealed CD+4 230 cells /Î¼L. Polymerase chain reaction (PCR) examination for HPV obtained HPV types 6 and 11 infections. Histopathologic examination revealed acanthosis, papillomatosis, and hyperkeratotic epidermis and koilocytotic cells. The patient was treated with electrodesiccation three times but obtained mass in anal getting bigger with a size of 6 x 3 x 3 cm. Therefore, he agreed to be referred to the surgical department with an extensive surgical excision plan. Screening of GCA using PCR is not a routine examination but PCR has high sensitivity and specificity for determining the type of HPV, is useful for determining GCA prognosis and therapy, and is recommended for malignant and possible GCA recurrence detection